Water-mediated hydrogen bonds and local side-chain interactions in the cooperative collapse and expansion of PNIPAM oligomers - Wanlin Chen; Martin Gruebele; Martina Havenith; Kurt J. Hebel; Carla Scaletti (Proceedings of the National Academy of Sciences, 2026)
Poly(N-isopropylacrylamide) (PNIPAM), a thermoresponsive homopolymer, is a well-established model for investigating coil-to-globule transitions. Here, we combine long molecular dynamics (MD) simulations, data sonification, and graph-theory analysis to elucidate the roles of intramolecular and PNIPAM–solvent hydrogen-bond (H-bond) patterns in the PNIPAM globule–coil equilibrium. Our analysis separates the driving forces for compaction into two contributions: the entropic gain from the loss of hydration water around hydrophobic patches and the enthalpic stabilization from water H-bonded to PNIPAM. We find that the role of the solvent in polymer compaction is more active and complex than has been previously assumed. Our observations indicate that direct, intrachain hydrogen bonds between amide groups (N–H···O=C) are not the primary stabilizing force. Instead, the collapsed globule contains an N–H···N network of local side-chain interactions and is stabilized by a dynamic network of persistent, long-distance water bridges, where individual water molecules form hydrogen bonds with multiple parts of the polymer chain.